PERBAIKAN PENURUNAN DAYA MAMPU DAN PEMELIHARAAN MESIN DIESEL KAPASITAS 1000 KW DI PLTD KOTO LOLO - Sulaeman Sulaeman (LP2M - Institut Teknologi Padang, 2015)
One of the most important power plant system is the diesel engine, where are the diesel engine include a conversion of energy that can be converted into the energy to change into the thermal that canbe burn in the combution chamber that will be mechanical energy. In this case, it has maximal power 1000 kW it will be able 500 until 600 kW. To evaluation that problem can use the maintenance at PLTD Koto Lolo PT PLN (Persero) Ranting Sungai Penuh will do the result of maintenance to do best.